2009
DOI: 10.1111/j.1365-2133.2009.09416.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow-growing melanoma: a dermoscopy follow-up study

Abstract: This study provides evidence for the existence of a subgroup of slow-growing melanomas, which may explain the increase in the incidence of thin melanoma, despite stable rates of thick melanoma and melanoma-associated mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 32 publications
(37 reference statements)
7
110
0
1
Order By: Relevance
“…Rapidly growing MMs, whose characteristics and associations were described by Liu et al [24], were more often symmetrical, elevated, amelanotic, symptomatic and with regular borders. In contrast, the study by Argenziano et al [4], based on a series of MMs that were excised after prolonged follow-up, provided evidence favouring the existence of a type of slow-growing MM, dermoscopically characterized by asymmetric pigmentation and overall reticular pattern. Several intermediate types of MMs may exist varying in their tendency to grow and metastasize, possibly corresponding to different dermoscopic aspects.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Rapidly growing MMs, whose characteristics and associations were described by Liu et al [24], were more often symmetrical, elevated, amelanotic, symptomatic and with regular borders. In contrast, the study by Argenziano et al [4], based on a series of MMs that were excised after prolonged follow-up, provided evidence favouring the existence of a type of slow-growing MM, dermoscopically characterized by asymmetric pigmentation and overall reticular pattern. Several intermediate types of MMs may exist varying in their tendency to grow and metastasize, possibly corresponding to different dermoscopic aspects.…”
Section: Discussionmentioning
confidence: 42%
“…In a follow-up study of 103 early MMs, including 49 MIS, Argenziano et al [4] noted that at baseline consultation the reticular pattern was the most common global dermoscopy feature observed in 62.1% of the lesions, followed by the unspecific (15.5%) and the multicomponent pattern (9.7%). An asymmetric distribution of colour and structure was noted in 68.6% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was evaluated on 100 dermoscopic images, and border detection error was calculated. Dermoscopic images for the initial consultation were analyzed by Argenziano et al [9] and were compared with images from the last follow-up consultation and the symmetrical/asymmetrical structural changes. Xie and Bovik [10] implemented a dermoscopic image segmentation approach by integrating the genetic algorithm (GA) and self-generating neural network (SGNN).…”
Section: Introductionmentioning
confidence: 99%
“…12 Argenziano et al and Salerni et al in two independent studies have found that in 58,3-65% of patients with slow growing melanoma the only dermocopic abnormality was enlargement of the lesion (more than 2 mm in 3 years -Argenziano et al). 11,13 Many experts, including Argenziano et al, suggest that in most cases only one follow-up visit should be conducted. If the dermatologist remains unsure about the nature of the lesion during the first follow-up visit, the lesion should be excised.…”
Section: Dermoscopy (And Videodermoscopy)mentioning
confidence: 99%